Dynamic Cournot-Type Oligopoly Models–A Correction - McManus, M. (Review of Economic Studies, 1962)
Journal Article Dynamic Cournot-type Oligopoly Models—A Correction Get access M. McManus M. McManus Birmingham Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 4, October 1962, Pages 337–339, https://doi.org/10.2307/2296312 Published: 01 October 1962